2022
DOI: 10.3389/fgene.2022.851384
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Pyroptosis-Related Gene Signature for Predicting Prognosis in Kidney Renal Papillary Cell Carcinoma

Abstract: Pyroptosis is defined as an inflammatory form of programmed cell death. Increasing studies have demonstrated that pyroptosis is closely related to tumor development and antitumor process. However, the role of pyroptosis in kidney renal papillary cell carcinoma (KIRP) remains obscure. In this study, we analyzed the expression of 52 pyroptosis-related genes (PRGs) in KIRP, of which 20 differentially expressed PRGs were identified between tumor and normal tissues. Consensus clustering analysis based on these PRGs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…Past research has employed consensus clustering to analyse gene expression data of kidney cancer. For instance, studies have explored gene expression related to ferroptosis in clear cell renal cell carcinoma [ 19 ], while in renal papillary cell carcinoma, gene expression associated with flame cell death has been researched [ 20 ]. Moreover, another study described the role of serine metabolism in papillary renal cell carcinoma and reported its relationship with tumour progression and immune suppression [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Past research has employed consensus clustering to analyse gene expression data of kidney cancer. For instance, studies have explored gene expression related to ferroptosis in clear cell renal cell carcinoma [ 19 ], while in renal papillary cell carcinoma, gene expression associated with flame cell death has been researched [ 20 ]. Moreover, another study described the role of serine metabolism in papillary renal cell carcinoma and reported its relationship with tumour progression and immune suppression [ 21 ].…”
Section: Introductionmentioning
confidence: 99%